A Review of the Effectiveness of the Integrated Solid Waste Management System in Institutional Solid Waste Management in Zimbabwe - Takunda Shabani; Steven Jerie (Research Square, 2022)
The review focuses on the effectiveness of the integrated institutional solid waste management system in Zimbabwe, utilising already published literature. Zimbabwean institutional solid waste is produced from schools, tertiary learning institutions, barracks, prisons, police camps and medical facilities. Institutional solid waste consist of plastics, papers, metals, textiles, rubber, food waste, glass and wood. Construction and demolition waste such as broken bricks, concrete, sand, stones are also produced from institutions. Medical institutions are sources of sharps, pathological, infectious, pharmaceutical, radioactive and cytotoxic solid waste. Institutions also discard electric and electronic waste such as computers and cell phones. Institutional solid waste management approaches in Zimbabwe are characterised by illegal dumping, co-storage of waste, ine